2015
DOI: 10.1093/jrr/rrv044
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new commercial single crystal diamond detector for photon- and proton-beam dosimetry

Abstract: A synthetic single crystal diamond detector (SCDD) is commercially available and is characterized for radiation dosimetry in various radiation beams in this study. The characteristics of the commercial SCDD model 60019 (PTW) with 6- and 15-MV photon beams, and 208-MeV proton beams, were investigated and compared with the pre-characterized detectors: Semiflex (model 31010) and PinPoint (model 31006) ionization chambers (PTW), the EDGE diode detector (Sun Nuclear Corp) and the SFD Stereotactic Dosimetry Diode De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 30 publications
8
35
1
6
Order By: Relevance
“…These findings show a major advantage of microDiamonds over natural diamond detectors and are in line with other studies where negligible dose‐rate dependence and deviations in signal stability within ±0.5% were observed for preirradiation doses below 3 Gy . Nevertheless, several authors observed individual behavior among microDiamond detectors and unusually high preirradiation doses of up to 12 Gy …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings show a major advantage of microDiamonds over natural diamond detectors and are in line with other studies where negligible dose‐rate dependence and deviations in signal stability within ±0.5% were observed for preirradiation doses below 3 Gy . Nevertheless, several authors observed individual behavior among microDiamond detectors and unusually high preirradiation doses of up to 12 Gy …”
Section: Resultssupporting
confidence: 91%
“…To assess this hypothesis, three microDiamond detectors were used to determine absorbed dose to water using two clinical HDR 192 Ir BT treatment delivery systems. The results presented in this paper will contribute to the development of HDR BT dosimetry and also complement the current characterization of microDiamond detectors …”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…LET‐value increases upto ~20 keV/μm, at the depth corresponding to the range 80%. As expected, results confirm the LET‐independent response observed in previous experimental work . Considering the uncertainties of the results, a LET dependence of the microDiamond detectors is not measurable and we conclude that there is agreement between the normalized response of the microDiamond detectors and the normalized response of Markus ionization chamber.…”
Section: Resultssupporting
confidence: 90%
“…In photon, electron and proton beams, this detector is described as suitable for small field dosimetry . Also in protons, most dosimetry studies conclude that the response of the PTW‐60019 microDiamond detector exhibits no LET dependence nor quenching effect (Mandapaka et al, Marinelli et al, Yuichi et al, Rossomme et al, Akino et al). In, which is based on an intercomparison of four microDiamond detectors in a clinical 138 MeV proton beam, authors reported a nonreproducibility between devices in terms of stability, sensitivity, and LET dependence.…”
Section: Introductionmentioning
confidence: 99%